ASP for minimal entailment in a rational extension of SROEL. Issue 5 (14th October 2016) - GIORDANO, LAURA; DUPRÉ, DANIELE THESEIDER
Abstract: In this paper we exploit Answer Set Programming (ASP) for reasoning in a rational extension SROEL (⊓, ×) R T of the low complexity description logic SROEL (⊓, ×), which underlies the OWL EL ontology language. In the extended language, a typicality operatorT is allowed to define conceptsT ( C ) (typical C 's) under a rational semantics. It has been proven that instance checking under rational entailment has a polynomial complexity. To strengthen rational entailment, in this paper we consider a minimal model semantics. We show that, for arbitrary SROEL (⊓, ×) R T knowledge bases, instance checking under minimal entailment is Π P 2 -complete. Relying on a Small Model result, where models correspond to answer sets of a suitable ASP encoding, we exploit Answer Set Preferences (and, in particular, the asprin framework) for reasoning under minimal entailment.